2004
DOI: 10.1152/ajprenal.00060.2004
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant stress in kidneys of spontaneously hypertensive rats involves both oxidase overexpression and loss of extracellular superoxide dismutase

Abstract: Oxidant stress is an important contributor to renal dysfunction and hypertension. We have previously demonstrated that regulation of renal oxygen consumption by nitric oxide (NO) is impaired in the kidney of spontaneously hypertensive rats (SHR) due to increased superoxide production. We further explored the mechanisms of enhanced oxidant stress in the kidney of SHR. Suppression of cortical oxygen consumption by bradykinin (BK) or enalaprilat (Enal), which act through stimulation of endogenous NO, was impaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
80
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 44 publications
3
80
1
1
Order By: Relevance
“…Tempol blunted all these effects of angiotensin II (55). Further, Adler and Huang showed that NO bioavailability in SHR is impaired due to an angiotensin II-mediated increase in superoxide production in association with enhanced expression of NADPH oxidase components (56). These results suggest that the oxidative stress induced by angiotensin II is associated with augmented oxygen consumption and subsequent hypoxia in the kidney.…”
Section: Oxidative Stressmentioning
confidence: 90%
“…Tempol blunted all these effects of angiotensin II (55). Further, Adler and Huang showed that NO bioavailability in SHR is impaired due to an angiotensin II-mediated increase in superoxide production in association with enhanced expression of NADPH oxidase components (56). These results suggest that the oxidative stress induced by angiotensin II is associated with augmented oxygen consumption and subsequent hypoxia in the kidney.…”
Section: Oxidative Stressmentioning
confidence: 90%
“…All three elements (ROS, angiotensin II, and proteinuria), in our opinion, could be sequentially responsible for the persistence of heparanase overexpression. Although the generation of ROS can be induced by angiotensin II (33)(34)(35), ROS also are thought to be induced by Adriamycin per se. The beneficial effects of DMTU treatment during the induction phase of AN support a role for ROS in the induction of changed charge-selective properties of the GBM, as a result of both a direct effect of ROS on HS and ROSinduced heparanase expression.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies indicate treatment with antioxidant supplements reduce oxidative stress during hypertension and kidney disease (1,18). In the present study, we sought to determine the role of ROS generation in contributing to the enhanced reactivity of isolated GA to ANG II.…”
Section: Mechanisms Of Enhanced Ang II Responsivenessmentioning
confidence: 96%